Salvia hunzikeri (Lamiaceae), a new species from the Andes of Peru - Granda Paucar, Arturo (2010)
Salvia hunzikeri (Lamiaceae), a new species restricted to Mantaro River valley in Peru, is described, illustrated, and its salient features contrasted to other species of section Flocculosae.